Meta-Analysis on Associations of Timing of Maternal Smoking Cessation Before and During Pregnancy With Childhood Overweight and Obesity. Issue 4 (15th September 2022) - Perkins, Jacob; Re, Tyler; Ong, Sherry; Niu, Zhongzheng; Wen, Xiaozhong
Abstract: Introduction: There is a lack of comprehensive review on associations of maternal smoking cessation (versus nonsmokers) with childhood overweight and obesity. Aims and Methods: We conducted a systematic review and meta-analysis of existing evidence in this field. Within PubMed, EMBASE, and CENTRAL databases, we identified and screened 1147 abstracts. We reviewed full-texts and extracted related information from 10 eligible articles. We pooled odds ratios for overweight/obesity and mean differences in BMI z-scores by maternal smoking status around pregnancy. Results: Among 10 eligible studies, 71 393 children were included from ages 2 to 18 years. Compared to children of nonsmokers, the pooled unadjusted odds ratio (OR) for overweight was 1.36 (95% Confidence Interval CI: 1.14, 1.62) in children of quitters and 1.44 (1.27, 1.64) in children of continued smokers. The pooled unadjusted OR for obesity was 1.65 (1.17, 2.32) in children of quitters and 1.94 (1.38, 2.73) in children of continued smokers. The pooled unadjusted mean difference in BMI z-score was 0.51 (0.41, 0.61) in children of quitters and 0.64 (0.58, 0.70) in children of continued smokers. The pooled unadjusted OR for overweight in children of mothers quitting before pregnancy was 1.46 (1.15, 1.85), during the first trimester was 1.52 (1.27, 1.82), and during pregnancy (mixed timing, mostly first trimester) was 0.97 (0.79, 1.20). Conclusion: The risk of offspring overweight and obesity was moderately higher for quitters during pregnancy compared to nonsmokers, although it might not be as high as continued smokers. Implications: Maternal smoking during pregnancy is an established risk factor of childhood overweight and obesity. Based on our systematic review, intervention to help mothers quit smoking has the potential to reduce the risk of childhood overweight and obesity in offspring related to prenatal tobacco exposure. Quitting before pregnancy is ideal, but quitting in early pregnancy is still helpful for reducing risk.